Hubungan Pemberian ASI Eksklusif dengan Kejadian Stunting pada Anak Balita - Stephanie Lexy Louis; Ayu Nina Mirania; Evi Yuniarti (Maternal & Neonatal Health Journal, 2022)
Stunting is a chronic nutritional problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with needs. Based on data in 2018, there were 17 districts/cities in South Sumatra that experienced stunting at the age of toddlers, one of which was the city of Palembang with a prevalence of 25.90%. There were 204 people with stunting in Palembang City in Talang Kelapa Village, 176 people in 14 Ulu and 139 people in 9/10 Ulu. ). Stunting can be anticipated by means such as exclusive breastfeeding until the age of 6 months, good nutritious food, a clean and healthy lifestyle, physical activity, and gradual monitoring of child development. This study aims to determine the relationship between exclusive breastfeeding and the incidence of stunting in children under five. This research is a type of analytic survey research and cross sectional approach. Samples were taken using random sampling technique. Data analysis using chi square test. The results of the study on the variable of exclusive breastfeeding obtained p value = 0.02 (<? = 0.05). The conclusion of this study is that there is a relationship between exclusive breastfeeding and the incidence of stunting in children aged 12-59 months with p = 0.002 (< = 0.05). Suggestions from this study are for mothers to be able to provide exclusive breastfeeding to their babies until the age of 6 months and continue breastfeeding until children are 2 years old and perform early detection of stunting by visiting health facilities, health workers at the Merdeka Health Center should maintain and improve the quality of health services in Indonesia. local work area.